Nucleolar accumulation of poly (A)+ RNA in heat-shocked yeast cells: implication of nucleolar involvement in mRNA transport. - Tani, T (1995)
Transport of mRNA from the nucleus to the cytoplasm plays an important role in gene expression in eukaryotic cells. In wild-type Schizosaccharomyces pombe cells poly(A)+ RNA is uniformly distributed throughout the nucleoplasm and cytoplasm. However, we found that a severe heat shock blocks mRNA transport in S. pombe, resulting in the accumulation of bulk poly(A)+ RNA, as well as a specific intron-less transcript, in the nucleoli. Pretreatment of cells with a mild heat shock, which induces heat shock proteins, before a severe heat shock protects the mRNA transport machinery and allows mRNA transport to proceed unimpeded. In heat-shocked S. pombe cells, the nucleolar region condensed into a few compact structures. Interestingly, poly(A)+ RNA accumulated predominantly in the condensed nucleolar regions of the heat-shocked cells. These data suggest that the yeast nucleolus may play a role in mRNA transport in addition to its roles in rRNA synthesis and preribosome assembly.